The application of Fourier transform near infrared (FT-NIR) spectroscopy in the wine, fruit and dried fruit industries of South Africa - Van Zyl, Anina (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc )--Stellenbosch University, 2000.